Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2005
DOI: 10.1002/yea.1282
|View full text |Cite
|
Sign up to set email alerts
|

Candida albicans SOU1 encodes a sorbose reductase required for L‐sorbose utilization

Abstract: Previous work in our laboratory showed that L-sorbose utilization in Candida albicans is subject to a novel form of regulation which involves a reversible increase or decrease in the copy number of chromosome 5. Furthermore, the structural gene SOU1 is required for L-sorbose utilization and encodes a member of the short chain dehydrogenase family. However, the precise function of SOU1 was not known and neither was the pathway for L-sorbose utilization. We have now expressed SOU1 at a high level from a replicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
33
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 33 publications
2
33
0
1
Order By: Relevance
“…The regions are scattered along Ch5, and the final number of regions is yet to be established. The monosomic condition of Ch5 downregulates, as expected, at least CSU51 (orf19.1105.2) and CSU53 (orf19.3931) from Ch5 and also upregulates SOU1 (sorbose utilization) from Ch4 that encodes sorbose reductase, which catalyzes the first step in the catabolic pathway of L-sorbose (11,13,14, and E. Rustchenko, unpublished data). Furthermore, antisense regulation of CSUs is involved, as at least CSU51 and CSU53 produce, in addition to sense transcripts, long noncoding antisense transcripts, designated ASUs (activation of sorbose utilization).…”
supporting
confidence: 69%
“…The regions are scattered along Ch5, and the final number of regions is yet to be established. The monosomic condition of Ch5 downregulates, as expected, at least CSU51 (orf19.1105.2) and CSU53 (orf19.3931) from Ch5 and also upregulates SOU1 (sorbose utilization) from Ch4 that encodes sorbose reductase, which catalyzes the first step in the catabolic pathway of L-sorbose (11,13,14, and E. Rustchenko, unpublished data). Furthermore, antisense regulation of CSUs is involved, as at least CSU51 and CSU53 produce, in addition to sense transcripts, long noncoding antisense transcripts, designated ASUs (activation of sorbose utilization).…”
supporting
confidence: 69%
“…A major part of the substrate is oxidized by membranebound PQQ-GLDH and FAD-SLDH, and then L-sorbose accumulates in the culture medium. After L-sorbose accumulates to some extent and D-sorbitol is exhausted, the cells start to utilize L-sorbose, probably similar to the case in C. albicans (8), through fructose 6-phosphate. During the accumulation of Lsorbose, SboR is expressed together with SboA and may compete with the unknown activator by binding to the same operator site for sboRA transcription; however, it probably does not repress its expression because of the presence of a derepressing molecule.…”
Section: Discussionmentioning
confidence: 83%
“…It has been reported that L-sorbose is incorporated into cells of Agrobacterium tumefaciens, Neurospora crassa, Aspergillus nidulans, and Candida albicans without phosphorylation (8). In contrast, in Escherichia coli, Lactobacillus casei, and Klebsiella pneumoniae, L-sorbose is phosphorylated to L-sorbose-1-phosphate at the cell surface during transport into the cell and reduced to D-sorbitol-6-phosphate by L-sorbose-1-phosphate reductase (26,27,30).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…They found that loss of chromosome 5 (Chr5) permitted growth on sorbose (53) and that subsequent reduplication of Chr5 under nonselective conditions reversed this phenotype. This phenotype is apparently due to multiple genes on the right arm of Chr5 that negatively regulate SOU1 (sorbose utilization 1), which is found on Chr4 (44,54).…”
mentioning
confidence: 99%